(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
This research attempts to evaluate the role of the information system by highlighting its importance in providing date and information to the tax administration the process of tax accounting for those who are subject to income tax whether they are individuals or companies where the effective information system provides accurate and reliable information in a timely manner. At the theoretical part of the research, the research approaches the problem of the research represented in that whether the information system, applied in the General Commission for Taxes, is capable of achieving its role in reducing the phenomenon of tax evasion. The existence of a set of things which in the Commission may lead to increase tax evasion by taxpayers. These things are represented in : the taxpayers’ names are similar, the absence of a unified database between the Commission and its branches in the provinces specified for taxpayer, the suspension of field survey committees, and the deactivating of the role the supporting administrations for tax administration.